Foregrounding Collaboration in Disciplinary Literacy: Implications from "JAAL," 2008-2017 - Hinton, KaaVonia; Suh, Yonghee (Journal of adolescent & adult literacy, 2019)
In this review, the authors examined articles on collaboration within the context of disciplinary literacy that appeared in the Journal of Adolescent & Adult Literacy between October 2008, when Moje published "Foregrounding the Disciplines in Secondary Literacy Teaching and Learning: A Call for Change," and December 2017. Findings suggest that the definition of disciplinary literacy has expanded, collaboration is important for both teacher and student learning, and tension surfaces when collaboration happens. The authors propose that greater attention needs to be given to the role of collaboration as a space to engage and enhance disciplinary literacy practices.